2015
DOI: 10.3109/09546634.2015.1083935
|View full text |Cite
|
Sign up to set email alerts
|

Superior efficacy of calcipotriene and betamethasone dipropionate aerosol foam versus ointment in patients with psoriasis vulgaris – A randomized phase II study

Abstract: Background: An aerosol foam formulation of fixed combination calcipotriene 0.005% (as hydrate; Cal) plus betamethasone dipropionate 0.064% (BD) was developed to improve psoriasis treatment. Objectives: To compare the efficacy and safety of Cal/BD aerosol foam with Cal/BD ointment after 4 weeks. Methods: In this Phase II, multicenter, investigator-blind, 4-week trial, adult patients with psoriasis vulgaris were randomized to Cal/BD aerosol foam, Cal/BD ointment, aerosol foam vehicle or ointment vehicle (3:3:1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
137
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 32 publications
12
137
2
4
Order By: Relevance
“…This may also explain why the treatment success rates at week 4 were lower in patients with mild disease compared to those with moderate and severe disease (18.9% vs. 44.8% and 50.0%, respectively). Importantly, the proportion of patients achieving mPASI75 at week 4 in PSO‐ABLE (52%) was comparable to that observed in previous studies (53% in PSO‐FAST,23 49% in one Phase II study24 and 50% in another Phase II study25). Based on the study protocol, patients who achieved treatment success were allowed to discontinue treatment, but were required to attend all scheduled visits until study end.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This may also explain why the treatment success rates at week 4 were lower in patients with mild disease compared to those with moderate and severe disease (18.9% vs. 44.8% and 50.0%, respectively). Importantly, the proportion of patients achieving mPASI75 at week 4 in PSO‐ABLE (52%) was comparable to that observed in previous studies (53% in PSO‐FAST,23 49% in one Phase II study24 and 50% in another Phase II study25). Based on the study protocol, patients who achieved treatment success were allowed to discontinue treatment, but were required to attend all scheduled visits until study end.…”
Section: Discussionsupporting
confidence: 84%
“…The safety profile of Cal/BD aerosol foam was similar to previous studies23, 24, 25 and was consistent with the fixed combination gel and ointment formulations 27, 28, 29. The rates of AEs and ADRs with Cal/BD aerosol foam in PSO‐ABLE cannot be compared to previous studies due to the longer observation period (12 vs. 4 weeks).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…34,32 Psoriasis' impact on HR-QoL was also assessed. Baseline Dermatology Life-Quality Index (DLQI) 33 for Cal/BD aerosol foam and vehicle groups were ACTH -Adrenocorticotropic hormone; ADRs -Adverse reactions; AEs -Adverse events; AUC -Area under the curve; DLQI -Dermatology Life-Quality Index; DTT -Difficult to treat; HR-QOL -Health-related quality of life; MDR -maximal dermal response; MCII -mean cumulative irritation index; mPASI -modified psoriasis area and severity index; pts -Patients; SAES -Serious adverse events; SD -Standard deviation; TCS -Total clinical score; y -Years 9.9 and 10.3, respectively, indicating a substantial impact on HR-QoL. 25 Mean baseline EQ-5D utility index scores indicated that the impaired QoL in these patients was due to significantly pain/discomfort and anxiety/depression compared with general population.…”
Section: Pso-fast Hr-qol Nct01866163mentioning
confidence: 99%